PENGARUH PEMANFAATAN PEMBELAJARAN BERBASIS ICT TERHADAP KREATIVITAS GURU DALAM MEMBUAT MEDIA PEMBELAJARAN - Desi Ratnasari; I Gede Sugiyanta; Dedy Miswar (JPG (Jurnal Penelitian Geografi), 2013)
The aim of this research was find out the influence of the use of Information Communication and Technology (ICT) to the teachers’ creativity in making learning media in XI grade students at SMA Negeri 1 Seputih Banyak, Central Lampung year of 2011-2012. As for the influence of the use of Information Communication and Technology (ICT) or the use of Information and Communication Technologies, whether they already have been used maximally in SMA Negeri 1 Seputih Banyak, Central Lampung.                                                 The reserarcher used descriptive quantitative methods with question form as the principal technique, as well as the supporting techniques i.e. interview and documentation, while the population was XI grade students of SMA Negeri 1 Seputih Banyak who are totally 48 students. The results of data analysis were: students declared the use of ICT-learning based in SMA Negeri 1 Seputih Banyak had good influence were 28 students (60.42%) of 48 respondents. And the students who declared that the teachers were creative in making learning media were more than half of the respondents, who were 26 students (54.17%) of 48 respondents.Key word:media, learning, creativity